Metaphysics of merchandise - Gil Claros, Mario Germán (2023)
Summary This text highlights your attention in the first part of the first volume of Capital. Vol. 1. (Marx, 1977) entitled merchandise and money, the metaphysical nature of merchandise, in which its mystical world is revealed in the social environment and that in one way or another hides its real origins in living human work, source of wealth and exploitation of contemporary societies.